PREVENCION Y ATENCION DE PERSONAS QUE VIVEN CON EL VIH-SIDA. GENDARMERIA DE CHILE Y MINISTERIO DE SALUD - CONASIDA. EVALUACION 2002 - 2005. - Vidal Bustos, María Soledad (Revista Chilena de Tecnología Médica, 2008)
Gendarmerie of Chile does not have been other people's to the development of the epidemic of AIDS in the country, world-wide pandemic that brought about by the human inmuno deficiency virus (HIV). This problematic one of public health was approached from the beginning creating a program directed to the control and the prevention of ITS-VIH-SIDA in the deprived people of freedom and living with HIV (PPL, PPL VVIH-SIDA) of the Chilean penitentiary enclosures, centralized in the estates of health of the institution and their Clinical Laboratory specifically. This program was favored with an agreement frame of joint work between Ministry of Health -- CONASIDA and Ministry of Justice -- Gendarmerie of Chile, signed year 2002, being this one the first evaluation (2002-2005), that gives account of the profits obtained in benefits of the PPL AND PPL VVIH-SIDA and whose results can generally be extrapolated benefits in the educative and preventive scope for the population.